Comparison of static and shake culture in the decolorization of textile dyes and dye effluents by Phanerochaete chrysoporium - Sani, R K; Azmi, W; Banerjee, U C (Folia microbiologica, 1998)
Decolorization of several dyes (Red HE-8B, Malachite Green, Navy Blue HE-2R, Magenta, Crystal Violet) and an industrial effluent with growing cells of Phanerochaete chrysosporium in shake and static culture was demonstrated. All the dyes and the industrial effluent were decolorized to some extent with varying percentages of decolorization (20-100%). The rate of decolorization was very rapid with Red HE-8B, an industrial dye. Decolorization rates for all the dyes in static condition were found to be less than the shake culture and also dependent on biomass concentration.
Keywords: Basidiomycota; Coloring Agents; chemické látky znečišťující vodu; Biodegradation, Environmental; Color; Textile Industry; Rosaniline Dyes; Water Pollutants, Chemical; textilní průmysl; průmyslový odpad; barvicí látky; Industrial Waste; mikrobiologické techniky; barva; genciánová violeť; Gentian Violet; Microbiological Techniques; rosanilinová barviva; biodegradace